Analisis Komoditas Unggulan Sektor Pertanian di Kabupaten Hulu Sungai Selatan Tahun 2012-2016 - Rasyid, Muhammad; Chandriyanti, Ika (JIEP: Jurnal Ilmu Ekonomi dan Pembangunan, 2019)
This research was conducted to (1) analyze the superior commodities of theagricultural sector in South Hulu Sungai Regency and (2) examine changes andstructural shifts in agricultural sector commodities.This study uses the Location Quotient (LQ) analysis tool to determine whatagricultural commodities are superior in South Hulu Sungai Regency and use ShiftShare analysis tools to find out changes and structural shifts of farm commoditiesinSouth Hulu Sungai Regency.The results of this study indicate that the leading agricultural commodities inthe South Hulu Sungai Regency are the food crops sub-sector: lowland rice, uplandrice, and sweet potato. Plantation sub-sectors: coconut, cocoa, clove, candlenut,kapok, sugar palm, cinnamon, rubber, and coffee. Fisheries sub-sector: cagecultivation and floating net culture. Forestry sub-sector: sawn wood. AnimalHusbandry Sub Sector: free-range chickens, pigs, and ducks. Based on shift-sharecalculation shows that the agricultural commodity which experienced the greatestchange or shift was found in the plantation sub-sector, namely the oil palmcommodity.